The Impact of Women Sexual Visualization in E-Sport Brand Ambassadors on Fan Engagement and Team Popularity - Sabatini, Yosica Gabrellia; Maharani, Angelia Brigita; Inayah, Rania (CV. Era Digital Nusantara, 2024)
This study aims to investigate the impact of the sexualized of women brand ambassadors in the e-sports industry on fan perception and engagement. It explores how the sexual visualization of women as brand ambassador shapes fan perceptions, loyalty, and their emotional connection with e-sports teams. This issue is particularly relevant in the context of popular culture and the broader societal debate about the commodification of women in media and entertainment. While e-sports has developed into a significant cultural phenomenon, the sexualized visualization of women brand ambassadors raises questions about its influence on fan loyalty, emotional connection, and perceptions of professionalism. Despite the increasing visibility of women in e-sports, there are still gaps in understanding how it shapes fan engagement and perception. This study uses qualitative methods by applying ethnography. This study use theory of circuit of culture by Hall. The data collection techniques in this study are in-depth interviews with 10 e-sports fans who are involved in e-sport field. The results show that the sexual visualization of women as Brand Ambassadors in e-sports has an initial influence in attracting fans attention, but their loyalty and engagement are not influence by BA sexual visualization, but based on team skill performance, and a balanced between professionalism and visuals in a BA. Fans perceive female BAs as centre of attention who have an attractive appearance, which often this sexuality of appearance is used as a commodification of female BAs in e-sports. This study provides insights into fans' perceptions of sexual representation, emphasizing the need for more balanced and empowering portrayals of women in e-sports. The findings highlight the importance of aligning visual strategy with professionalism to increase inclusivity and sustain meaningful engagement in the e-sports community.